2023
DOI: 10.3390/molecules28020748
|View full text |Cite
|
Sign up to set email alerts
|

Taste Masking of Promethazine Hydrochloride Using l-Arginine Polyamide-Based Nanocapsules

Abstract: Promethazine hydrochloride (PMZ), a potent H1-histamine blocker widely used to prevent motion sickness, dizziness, nausea, and vomiting, has a bitter taste. In the present study, taste masked PMZ nanocapsules (NCs) were prepared using an interfacial polycondensation technique. A one-step approach was used to expedite the synthesis of NCs made from a biocompatible and biodegradable polyamide based on l -arginine. The produced NCs had an average particle size of 193.63 ± 39.1 nm and a zeta potential of −31.7 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…4d did not reveal any endothermic peak of TQ while the shallow peaks of the glass transition and evaporation are still present. It is proposed that TQ may have transformed into an amorphous material, hence an improved solubility, or the drug is encapsulated within the polymer as reported by other researchers [36,49].…”
Section: Thermal Profile Analysis Using Dscmentioning
confidence: 86%
See 1 more Smart Citation
“…4d did not reveal any endothermic peak of TQ while the shallow peaks of the glass transition and evaporation are still present. It is proposed that TQ may have transformed into an amorphous material, hence an improved solubility, or the drug is encapsulated within the polymer as reported by other researchers [36,49].…”
Section: Thermal Profile Analysis Using Dscmentioning
confidence: 86%
“…These polymers have been used as carriers to facilitate insulin transdermal delivery, improve medication diffusion and distribution via the skin [35], and successfully deliver high doses of TQ into the lungs using dry powder inhalers [7]. Additionally, L-arginine-based polyamide was used to encapsulate promethazine HCl and produce taste-masked nanoparticles [36], while unsaturated L-arginine-poly(ester amide)s in an aqueous solution were used to create cationic hydrogels [37]. In recent studies, L-arginine-based polymers were found to be effective in gene transportation, gene condensation, and release [38].…”
Section: Introductionmentioning
confidence: 99%
“…The other phase consists of terephthaloyl chloride and CBZ in chloroform (CHCl 3 ). Using this method, direct encapsulation of CBZ resulted in capsules with an average diameter around 400 nm and high-efficiency drug loading of 19.8% [52].…”
Section: Synthesis Of Poly(ester-amide) Carbamazepine Formula [(Cbz/a...mentioning
confidence: 99%